2016
DOI: 10.3389/fmicb.2016.00142
|View full text |Cite
|
Sign up to set email alerts
|

Multiple ESBL-Producing Escherichia coli Sequence Types Carrying Quinolone and Aminoglycoside Resistance Genes Circulating in Companion and Domestic Farm Animals in Mwanza, Tanzania, Harbor Commonly Occurring Plasmids

Abstract: The increased presence of extended-spectrum beta-lactamase (ESBL)-producing bacteria in humans, animals, and their surrounding environments is of global concern. Currently there is limited information on ESBL presence in rural farming communities worldwide. We performed a cross-sectional study in Mwanza, Tanzania, involving 600 companion and domestic farm animals between August/September 2014. Rectal swab/cloaca specimens were processed to identify ESBL-producing Enterobacteriaceae. We detected 130 (21.7%) ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
83
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(102 citation statements)
references
References 34 publications
14
83
3
2
Order By: Relevance
“…The virulence and resistant genes found in APEC have been detected on IncFIB plasmids, such as pAPEC-1 (Mellata et al, 2012). All plasmid replicons reported in the current study have been previously detected in E. coli isolates sourced from the environment, other animals and humans (Bortolaia et al, 2010;Garcia-Fernandez et al, 2008;Kluytmans et al, 2013;Lynne et al, 2012;Seni et al, 2016;Wang et al, 2013a;Woodford et al, 2007).…”
Section: Investigating the Prevalence Of Carriage Of Avian Pathogenicsupporting
confidence: 53%
See 1 more Smart Citation
“…The virulence and resistant genes found in APEC have been detected on IncFIB plasmids, such as pAPEC-1 (Mellata et al, 2012). All plasmid replicons reported in the current study have been previously detected in E. coli isolates sourced from the environment, other animals and humans (Bortolaia et al, 2010;Garcia-Fernandez et al, 2008;Kluytmans et al, 2013;Lynne et al, 2012;Seni et al, 2016;Wang et al, 2013a;Woodford et al, 2007).…”
Section: Investigating the Prevalence Of Carriage Of Avian Pathogenicsupporting
confidence: 53%
“…The IncI1, IncFIB, IncY and IncN plasmids have been identified in poultry previously and were associated with MDR and ESBLs producing E. coli (Bortolaia et al, 2010;Garcia-Fernandez et al, 2008;Kluytmans et al, 2013;Lynne et al, 2012;Seni et al, 2016;Wang et al, 2013a). One of the ESC resistant isolates contained IncY and IncI1 plasmid types, while the other contained IncFIA, IncFIB and IncFrep plasmids.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have reported on the coexistence of carbapenemases, ESBLs, and AMEs in Enterobacteriaceae (29)(30)(31)(32)(33)(34). Genes encoding AMEs have been found on the same plasmids and integrons as genes encoding KPC or ESBLs (35)(36)(37)(38)(39). Less commonly, KPC and ESBL genes may coexist on the same plasmids (37,40).…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed in this hospital have shown high rates of ESBL-producing K. pneumoniae and E. coli carrying bla CTX-M-15 in IncF plasmids (Mshana et al, 2011, 2013). In addition recent studies involving isolates from animals and humans from community have shown the bla CTX-M-15 allele to be predominant (Mshana et al, 2016; Seni et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Evidence in the literature has also documented the probable horizontal transfer of resistance genes from either human sewage or clinical isolates to fish in rivers or lakes in which drainage of wastewater from treatment plants occurs (Kümmerer, 2009; Martinez, 2009b; Jiang et al, 2012; Blaak et al, 2014). Multiple genotypes of ESBL-producing E. coli have been found in animals and humans in Mwanza (Mshana et al, 2011, 2016; Seni et al, 2016). There are few studies from developed countries on the presence of ESBL-producing isolates in fish and environment samples and the role played by the food chain in transmission of resistance genes through contamination by human and animals sewage and anthropogenic activities in relation to water bodies (Zurfluh et al, 2013; Abgottspon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%